TOWARDS SECURE IOT: A FRAMEWORK FOR AUTHENTICATION, ACCESS CONTROL, AND DATA INTEGRITY - Vaidehi Shah; Dr. Vijaykumar B Gadhavi (International Educational Journal of Science and Engineering, 2025)
The rapid expansion of the Internet of Things (IoT) has enabled transformative connectivity and automation across multiple domains. However, this growth also introduces critical security vulnerabilities, particularly in resource-limited IoT environments. Ensuring strong authentication, granular access control, and data integrity is essential to safeguard such systems. This paper proposes a lightweight and comprehensive security framework specifically designed for IoT networks. The framework incorporates secure device authentication mechanisms, adaptive access control policies, and cryptographic techniques to preserve data integrity during transmission. It is architected to be both scalable and interoperable, making it suitable for diverse and heterogeneous IoT ecosystems. Through simulation-based evaluations under a range of threat scenarios, we assess the framework’s effectiveness in preventing unauthorized access, ensuring message authenticity, and mitigating data tampering, all while maintaining low computational and energy overhead. The results affirm that the proposed solution is highly appropriate for real-time, low-power IoT applications where security is paramount.